STUDENTSâ VS. TEACHERSâ PERSPECTIVES ON BEST TEACHER CHARACTERISTICS IN EFL CLASSROOMS - Nihta V F Liando (TEFLIN, 2010)
Abstract: This paper discusses the perspectives of students and teachers in a university setting about best teacher characteristics. This is viewed through the perspectives of students and teachers regarding their perceptions of qualities of English teachers, and teachersâ immediacy behavior â verbal or non-verbal - as predictors of student academic motivation. In this study, 126 students and 28 teachers in the English department at State University of Manado, Indonesia were involved. From the questionnaire, this study proved that a teacher was an important personnel in EFL teaching. Both teacher and students believed that a good teacher should display personal and academic attitudes. Both parties also considered that there were certain verbal and nonverbal immediacy behaviors teachers performed which could be the source of motivating as well as de-motivating the students. This study is expected to give understanding of how teaching English in a foreign language context can be better.